Legal Protection of Patients' Rights Toward Quality Improvement and Patient Safety at Accredited Hospital - Santosa, Agung; Durahman, Dani; Sutiamah, Titi; Wulan Sari, Febilita (Greenation Research & Yayasan Global Resarch National, 2024)
Hospital Accreditation is an acknowledgment of the Minister of Health through the Hospital Accreditation Committee (an independent assessment agency), that the Hospital has met the quality service standards constinously. Research was conducted on the topic of service quality and patient safety at the Sartika Asih Hospital Bandung (RSBSA) in 2019 and 2020. The purpose was to obtain secondary data on the implementation of quality and patient safety indicators, service complaints data and solutions offered, also data on patient satisfaction. In January to March 2021, about 450 respondents were taken to see their perceptions on hospital services based on the primary data. Hospital failure to meet minimum service standards according to predetermined indicators can lead to the failure of therapeutic contract. This is supported by the Hospital Law Number 44 Year 2009 Article 32 letter (q) which states: every patient has the right to sue and/or sue the hospital, if the hospital is suspected of providing services that are not in accordance with standards, both civil and criminal. Thus, a violation of the rules might result in a lawsuit. With the preventive and repressive legal protection, it is hoped that the patients’ rights to quality and safety can be fulfilled by the hospital.